2009
DOI: 10.1016/j.jtcvs.2009.04.063
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, crossover pilot study of inhaled nitric oxide versus inhaled prostacyclin in heart transplant and lung transplant recipients

Abstract: In heart transplant and lung transplant recipients, nitric oxide and prostacyclin similarly reduce pulmonary artery pressures and central venous pressure, and improve cardiac index and mixed venous oxygen saturation. Inhaled prostacyclin may offer an alternative to nitric oxide in the treatment of pulmonary hypertension in thoracic transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 26 publications
2
103
0
Order By: Relevance
“…501 The short-term effects of inhaled PGI 2 , milrinone, and nitroglycerin may be as effective as iNO at lowering PVRI and improving intrapulmonary shunt fraction with minimal decreases in systemic hemodynamics. 294,[501][502][503][504] In a placebo-controlled trial, intravenous sildenafil reduced PAP and shortened the time to extubation and intensive care unit stay without adverse events in children after cardiac surgery. 475 A randomized, prospective trial in children compared intravenous sildenafil with iNO therapy and reported augmentation of pulmonary vasodilation with combined treatment.…”
Section: Pah-specific Drug Therapy Of Acute Postoperative Phmentioning
confidence: 99%
“…501 The short-term effects of inhaled PGI 2 , milrinone, and nitroglycerin may be as effective as iNO at lowering PVRI and improving intrapulmonary shunt fraction with minimal decreases in systemic hemodynamics. 294,[501][502][503][504] In a placebo-controlled trial, intravenous sildenafil reduced PAP and shortened the time to extubation and intensive care unit stay without adverse events in children after cardiac surgery. 475 A randomized, prospective trial in children compared intravenous sildenafil with iNO therapy and reported augmentation of pulmonary vasodilation with combined treatment.…”
Section: Pah-specific Drug Therapy Of Acute Postoperative Phmentioning
confidence: 99%
“…The inhalation of these agents appears to be superior to a systemic administration of prostaglandins or other pulmonary vasodilators as the pulmonary artery bed is widened more selectively and systemic vasodilation and consequent systemic hypotension can be prevented. 11 The newly transplanted heart needs appropriate filling pressures, being completely preload dependent. However high central venous pressures and right ventricular overdistension should be avoided.…”
Section: The Calculation Of the Pulmonary Artery Vascular Resistance mentioning
confidence: 99%
“…Inhaled epoprostenol is generally the preferred agent in the ICU setting given its short half-life and ease of use [28]. Inhaled epoprostenol improves pulmonary artery pressures and cardiac index comparably to inhaled nitric oxide in patients with right heart failure after heart and lung transplantation and may be more effective at reducing afterload in patients with pulmonary hypertension [44][45][46]. Inhaled prostacyclins are generally more cost-effective than inhaled nitric oxide and have become the preferred inhaled pulmonary vasodilator in many centers.…”
Section: Afterload Reductionmentioning
confidence: 99%